2023
DOI: 10.1093/europace/euad018
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation improved ejection fraction in persistent AF patients: a DECAAF-II sub analysis

Abstract: Aims The aim of our study was to assess differences in post-ablation atrial fibrillation (AF) recurrence and burden and to quantify the change in LVEF across different congestive heart failure (CHF) subcategories of the DECAAF-II population. Methods and results Differences in the primary outcome of AF recurrence between CHF and non-CHF groups was calculated. The same analysis was performed for the three subgroups of CHF and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…| 723 simultaneously examining the outcomes of catheter ablation across the spectrum of three HF subcategories. 68 Overall, our analyses have shown that the presence of AF significantly accentuate the risks of hard clinical endpoints in the different HF subcategories, especially in HFpEF and HFmrEF. Our results provide rationale for future studies evaluating treatments including ablation and their outcomes across the three HF subcategories.…”
Section: F I U R Ementioning
confidence: 65%
See 1 more Smart Citation
“…| 723 simultaneously examining the outcomes of catheter ablation across the spectrum of three HF subcategories. 68 Overall, our analyses have shown that the presence of AF significantly accentuate the risks of hard clinical endpoints in the different HF subcategories, especially in HFpEF and HFmrEF. Our results provide rationale for future studies evaluating treatments including ablation and their outcomes across the three HF subcategories.…”
Section: F I U R Ementioning
confidence: 65%
“…It has been observed that there is no difference between efficacy and safety outcomes of catheter ablation between HFpEF and HFrEF 66,67 . There have not been many studies simultaneously examining the outcomes of catheter ablation across the spectrum of three HF subcategories 68 …”
Section: Discussionmentioning
confidence: 99%
“…BNP is a widely used biomarker of HF and elevated levels have diagnostic and clinical utility among individuals with HF 10 . Several variables are predictive of arrhythmia recurrence following ablation, including age, left atrial volume, and duration of AF 10–12 . Even though natriuretic peptides are primarily produced by ventricular myocytes, atrial secretion of BNP is increased in individuals with AF 13 .…”
Section: Discussionmentioning
confidence: 99%
“…10 Several variables are predictive of arrhythmia recurrence following ablation, including age, left atrial volume, and duration of AF. [10][11][12] Even though natriuretic peptides are primarily produced by ventricular myocytes, atrial secretion of BNP is increased in individuals with AF. 13 Natriuretic peptides may be predictive in AF due to changes in the left atrium, including increased pressure and volume, fibrosis, hypertrophy, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard diagnosis of AF is 12-lead ECG recording. Since the examination is difficult to perform in mass field surveys, several tools have been validated for screening with convincing reliability [5][6][7][8][9][10][11][12][13][14]. We used Alivecor Kardia software embedded on a smartphone with the aim to explore the epidemiological profile of AF a poorly recognized disease among the general Congolese partly because such information is not yet available.…”
Section: Introductionmentioning
confidence: 99%